Corporate Governance Mechanism: Its Role Against the Criteria for Sharia Stocks and Share Prices - Moch. Edman Syarief; Dadang Hermawan; Leni Nur Pratiwi (Universitas Pendidikan Indonesia, 2022)
Purpose - This study examines the effect of corporate governance mechanisms represented by the number of board of commissioners and board of directors on the fulfillment of sharia stock criteria and stock prices. Methodology - The data collected from 195 Islamic issuers listed on the Indonesian Sharia Stock Index with the observation period of the 2012- 2016 on the annual report. The analytical tool used is a robust path analysis using WARP PLS. Findings - The results of the study state that there is a direct influence of the corporate governance mechanism on the fulfillment of sharia stock criteria, there is an indirect influence from the board of commissioners through the board of directors on sharia stock criteria, but there is no indirect influence on stock prices. The average value of TUBTA and NPI is well below the maximum limit set by OJK, and there is no sharia compliance officer in the company under study. The existence of compliant sharia officers may be a solution for differences in the influence that occurs between the commissioner's board and the board of directors on the fulfillment of Islamic finance criteria.Keywords: Board of commissioners; board of directors; sharia stock financial criteria; stock prices.